Austenite transformation during deformation of additively manufactured H13 tool steel. (December 2022) - Chadha, Kanwal; Tian, Yuan; Nyamuchiwa, Kuda; Spray, John; Aranas, Clodualdo
Abstract: This investigates the austenite transformation in additively manufactured, H13 tool steel, which exhibits a combination of high hardness, toughness, and resistance to high operating temperatures. The alloy was fabricated using the laser powder bed fusion (LPBF) technique. As-printed and heat-treated specimens in their undeformed and tensile tested conditions were analyzed using electron backscatter diffraction (EBSD) techniques. It was identified that in the as-printed specimen, the retained austenite phase fraction was 26.9%, which dropped to 1.66% following heat treatment. The mechanical test results revealed that the austenite fraction, as well as carbide precipitation, affects the strength and ductility of the LPBF-fabricated H13 tool steel. In order to further investigate the strengthening mechanism, a detailed microstructural analysis of the deformed sample was also carried out. As expected, it was observed that the metastable austenite phase dynamically transforms to martensite. To explain this phenomenon, the Gibbs energy associated with dislocations generated by tensile testing at room temperature was calculated. This stored energy was then compared to the theoretical Gibbs energy needed for the phase transformation to occur. The results show that the Gibbs energy due to dislocation density can explain the observed diffusionless dynamic phase transformation. Graphical Abstract: ga1